Prudence in the Anthropocene - Hariman, Robert (Journal for the history of rhetoric (Print), 2024)
The deliberative judgment referred to in the history of rhetoric as phronesis, practical wisdom, or prudence might have prevented the existential crisis of the Anthropocene era, but it seems unable to reverse the damage or provide a basis for ecological sustainability. This essay offers several considerations for adapting this traditional model of judgment to take up the new challenge. The normative, calculative, and performative modalities of prudential thinking, along with insights provided by the Chinese philosopher Xu Changfu, provide a basis for examining political, technocratic, ethical, and artistic mentalities for addressing global warming, assessing their strengths and weaknesses in respect to effective advocacy, and learning from them to improve and expand practical wisdom. Special emphasis is given to paying attention to art, artists, and aesthetic values on behalf of developing an attitude of ecological mindfulness.